A Deposition Rate-Based Index of Debris Concentration and its Extraction Method for Online Image Visual Ferrography. Issue 6 (2nd November 2021) - Fan, Bin; Liu, Yong; Zhang, Chao; Wang, Jianguo; Zhang, Peng; Mao, Junhong
Abstract: Online image visual ferrography (OLVF) is an acquisition method for oil debris information, which is affected significantly by the aggregation and overlap of wear debris and air bubbles in practice. In this work, a debris deposition video from OLVF is recorded as raw data. A relationship between wear debris concentration and debris deposition rate in a deposition process of OLVF is derived. Based on this, a deposition rate-based index of debris concentration (IDC) from OLVF video is proposed. A matching algorithm is developed to calculate the IDC. Moreover, a full-life accelerated gear wear test is performed, in which in total 1505 bubble-debris videos are obtained by OLVF. The verification results show that the approach not only can overcome the interference of air bubbles but also can avoid the error of saturation nonlinearity caused by agglomeration and overlap of wear debris, and that the proposed IDC performs better than the previously used index of particle coverage area (IPCA).